A retrospective study on the epidemiological characteristics and establishment of an early warning system of severe COVID‐19 patients. Issue 10 (2nd June 2020) - Yang, Ping; Wang, Pengfei; Song, Yuyan; Zhang, An; Yuan, Guodan; Cui, Yong
Abstract: This paper estimates the magnitude of an informational friction limiting credit reallocation to firms during the 2007‐2009 financial crisis. Because lenders rely on private information when deciding which relationship to end, borrowers looking for a new lender are adversely selected. I show how to identify private information separately from information common to all lenders but unobservable to the econometrician by using bank shocks within a discrete choice model of relationships. Quantitatively, these informational frictions seem too small to explain the credit crunch in the U.S. syndicated corporate loan market.